Developing micro-Raman spectroscopy for char structure characterization in the scale of micro- and bulk: A case study of Zhundong coal pyrolysis. (1st May 2021) - Xu, Jun; Xiang, Xingrui; Xu, Kai; He, Limo; Han, Hengda; Su, Sheng; Wang, Yi; Hu, Song; Xiang, Jun
Graphical abstract: Highlights: Raman mapping technology was developed for char structure characterization. More than 150 individual particles in micro-scale were studied for each sample. H/C atom ratio of individual char particle in micro-scale was quantified. Structure evolution characteristics during Zhundong coal pyrolysis was revealed. Abstract: Heterogeneity of coal in micro-scale is significant and can affect coal thermal behavior. In this study, micro-Raman spectroscopy was developed for characterizing coal/char in the scale of micro- and bulk with a case study of Zhundong coal pyrolysis. More than 150 particles in micro-scale were analyzed for each sample by micro-Raman mapping technology controlled by a computer program. Individual Raman spectrum of each particles in micro-scale and average Raman spectrum for each sample were analyzed, respectively. The results indicate that the evolution characteristics of aromatic rings, C–H in methyl or methylene, and C = O groups can be revealed by combined deconvolution of first- and second-order Raman spectrum. The fluorescence interference in Raman spectrum defined as drift coefficient α can quantitate volatiles content and H/C atom ratio of individual coal/char particle in micro-scale. The results reveal that the chemical structures of the Zhundong coal in micro-scale are significantly heterogeneous. The structural evolution of char particle in micro-scale differs from each other, especially in the early stage of the Zhundong coal pyrolysis. The chemical structure of char particles in micro-scale tends to converge as the pyrolysis progresses. A more severe pyrolysis condition can generally lead to a char with higher heterogeneity. For the bulk structural evolution, the Zhundong coal pyrolysis can be mainly divided into two stages. Firstly, the C–H in methyl or methylene releases rapidly, and the relative amount of small aromatic rings and C = O groups decrease mildly. And then, the aromatization degree of char increases rapidly along with the significant release of C = O groups.